2020
DOI: 10.1371/journal.pone.0243373
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and related factors of emergency department visits, readmission, and hospital transfers of inpatients under a DRG-based payment system: A nationwide cohort study

Abstract: Objectives Taiwan has implemented the Diagnosis Related Groups (DRGs) since 2010, and the quality of care under the DRG-Based Payment System is concerned. This study aimed to examine the characteristics, related factors, and time distribution of emergency department (ED) visits, readmission, and hospital transfers of inpatients under the DRG-Based Payment System for each Major Diagnostic Category (MDC). Methods We conducted a retrospective cohort study using data from the National Health Insurance Research D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…However, the summary metric scores of TCVH, ̅̅̅̅̅̅ , ̅̅̅̅̅̅̅̅ , and ̅̅̅̅̅̅̅̅ suggest that Hospital B performed at a higher level than Hospital A, even though the average cost of Hospital B (10,656) was slightly higher than that of Hospital A (10,572). As an emergency hospital, Hospital A has a different structure to Hospital B that aligns with other studies [39,40].…”
Section: Top Down Evaluation Using Regional Benchmarkssupporting
confidence: 53%
“…However, the summary metric scores of TCVH, ̅̅̅̅̅̅ , ̅̅̅̅̅̅̅̅ , and ̅̅̅̅̅̅̅̅ suggest that Hospital B performed at a higher level than Hospital A, even though the average cost of Hospital B (10,656) was slightly higher than that of Hospital A (10,572). As an emergency hospital, Hospital A has a different structure to Hospital B that aligns with other studies [39,40].…”
Section: Top Down Evaluation Using Regional Benchmarkssupporting
confidence: 53%
“…The electronic medical record captured patient status (dead/alive) for all-cause mortality. Although patients may have died at an outside hospital with a separate electronic medical record, we believe the prevalence is low as a previous study of readmissions in Taiwan using the government’s National Health Insurance Research Database found that only 0.16% of readmissions occurred at a different hospital 12 . Moreover, we ensured the censored patients were alive at the last known hospital encounter.…”
Section: Methodsmentioning
confidence: 88%